Teachers’ Capabilities in Implementing Inclusive Education: A South African Perspective - Mokhampanyane, Matsolo (Research in Social Sciences and Technology- OpenED Network, 2024)
In this empirical paper, we discuss teachers’ capabilities in implementing inclusive education. The background to this paper is that teachers have challenges in implementing inclusive education in South African primary schools. The study is underpinned by critical emancipatory research (CER), which advocates for peace, hope, equality, freedom, and social justice. A transformative paradigm under a qualitative approach and participatory action research design was adopted to analyze the experiences of the stakeholders of the research school. This is a qualitative paper where interviews were used to collect data from 7 participants. The study found that teachers in primary schools are not well prepared to implement inclusive education. Considering the findings, the study argues that there is a need to ensure that teachers are well-prepared and supported for inclusive education through in-service training.